The effect of social entrepreneurs' human capital on and firm performance: The moderating role of specific human capital - Youngkeun Choi; Sugin Chang (Cogent Business & Management, 2020)
This study applies human capital theory to link social entrepreneurs' characteristics and the performance of social ventures. Especially, considering the dualistic nature of social ventures, we investigate two specific human capital of entrepreneurs, such as prior social experience and prior commercial experience. These are associated with the venture's goal of social mission and profit generation, respectively. In the Korean context, social enterprises have another function to provide jobs and increase employment rates in the time of low economic growth and economic inequality. Given this situation, it is necessary that researchers investigate what human capitals of social entrepreneurs are helpful to obtain better social and commercial performance and what specific human capitals may have moderating effects on the relationship between the human capitals of social entrepreneurs and the social and commercial performance of social ventures. In the results, first, that the younger, the highly educated, or from more prestigious universities social entrepreneurs are, the better social performance their social ventures show. Second, the younger, the highly educated, or from more prestigious universities social entrepreneurs are, the better commercial performance their social ventures show. Third, when social entrepreneurs with prior social experience graduates from more prestigious, the better social performance their social ventures show than others. Finally, when social entrepreneurs with prior commercial experience have output function background, the better commercial performance their social ventures show than others.
Keywords: 650; social venture; social entrepreneurs; human capital theory; prior social experience; prior commercial experience